Morphological Analysis and Composition of Natural, Ivory, and Oily Types of Ms Glow Powder Using Scanning Electron Microscope (SEM) and X-Ray Fluorescence (XRF) - Puspita, Vela; Deswardani, Frastica; Afrianto, M. F; Selamat, N. Shazleen Nadia (PUI BiGME Universitas Jambi, 2025)
This research was conducted to determine the morphology and composition of loose powder. This research used 3 types of MS Glow brand loose powder, namely natural, ivory and oily. Morphological characterization was carried out using a Scanning Electron Microscope (SEM), while composition was carried out using X-Ray Fluorescence (XRF). The morphology of the MS Glow brand loose powder of the ivory, Natural and Oily types is round in shape with the average particle size of each sample A, B and C, namely 62 nm, 48 nm and 47 nm so that it can be classified as nanoparticles. XRF test results show that all samples contain the elements Mg, Al, Si, K, Ti, Fe. All of these elements are contained in the composition of MS Glow brand loose powder. The XRF test also showed that all samples did not contain dangerous elements such as Lead (Pb), mercury (Hg) and Cadmium (Cd) and met BPOM standards.